Smart surgeons sharp decisions cognitive skills to avoid errors & achieve results - Shiralkar, Uttam (Surgical psychology series., 2011)
Offers findings from decision science that surgeons, irrespective of speciality or seniority, can apply to everyday practice. This title offers answers to the questions which experienced surgeons may find difficult to explain.